2014
DOI: 10.1055/s-0033-1356424
|View full text |Cite
|
Sign up to set email alerts
|

Therapy Response Evaluation of Malignant Lymphoma in a Multicenter Study: Comparison of Manual and Semiautomatic Measurements in CT

Abstract: Abdomen 768Weßling J et al. Purpose:Comparison of manual one-/bi-dimensional measurements versus semi-automatically derived one-/bi-dimensional and volumetric measurements for therapy response evaluation of malignant lymphoma during CT follow-up examinations in a multicenter setting. Materials and Methods: MSCT data sets of patients with malignant lymphoma were evaluated before (baseline) and after two cycles of chemotherapy (follow-up) at radiological centers of five university hospitals. The long axis diame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Nonetheless, if possible, one examiner should be assigned to each patient and kept consistent to at least avoid interobserver variability in studies. Studies have since been able to show that semiautomatic measurement was significantly more accurate for response evaluation in lymphoma than the manual measurement method [39,40].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, if possible, one examiner should be assigned to each patient and kept consistent to at least avoid interobserver variability in studies. Studies have since been able to show that semiautomatic measurement was significantly more accurate for response evaluation in lymphoma than the manual measurement method [39,40].…”
Section: Discussionmentioning
confidence: 99%
“…Even if a return to one-dimensional measurement of lesions is recommended in the latest RECIL classification for simplification, the role of the volumetric measurement of target lesions for lymphomas should also be examined in the future. This is particularly true in light of the increasingly better functioning of automatic volumetry [39,40]. Volumetric limits have already been calculated for RECIST 1.1.…”
Section: Discussionmentioning
confidence: 99%
“…Both the steadily growing number of interdisciplinary tumor centers (Comprehensive Cancer Center: CCC), as well as the increasing mobility of cancer patients who are occasionally treated in two or more different centers lead to the radiological assessment of the same patient by different radiologists at various locations. Some single-and multi-center examinations have already demonstrated that this course of action, i. e. manual and/or one-dimensional evaluation of malignant lesions by several radiologists results in high inter-and intra-observer variability [17,44], and that semi-automated determination of multi-dimensional parameters can reduce the rate of misclassification of the therapeutic response [45]. Together with recent advances in CT technology, this knowledge has led to the development of software that can be used to measure and segment lesions semi-automatically ( • " Fig.…”
mentioning
confidence: 99%